2021
DOI: 10.1371/journal.pone.0260557
|View full text |Cite
|
Sign up to set email alerts
|

Long-term retention and predictors of attrition for key populations receiving antiretroviral treatment through community-based ART in Benue State Nigeria: A retrospective cohort study

Abstract: Background Key populations (KP) are disproportionately infected with HIV and experience barriers to HIV care. KP include men who have sex with men (MSM), female sex workers (FSW), persons who inject drugs (PWID) and transgender people (TG). We implemented three different approaches to the delivery of community-based antiretroviral therapy for KP (KP-CBART) in Benue State Nigeria, including One Stop Shop clinics (OSS), community drop-in-centres (DIC), and outreach venues. OSS are community-based health faciliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This is a cause for concern as this is a high-risk group which has the propensity to facilitate transmission of HIV in the population. Previous studies have shown a similar pattern of high LTFU among FSWs [ 16 , 17 ]. A retrospective cohort study in Côte d’Ivoire among FSWs found low levels of retention on ART of 75% after 6 months of initiation on ART and this dropped to 68% at 12 months [ 16 ].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…This is a cause for concern as this is a high-risk group which has the propensity to facilitate transmission of HIV in the population. Previous studies have shown a similar pattern of high LTFU among FSWs [ 16 , 17 ]. A retrospective cohort study in Côte d’Ivoire among FSWs found low levels of retention on ART of 75% after 6 months of initiation on ART and this dropped to 68% at 12 months [ 16 ].…”
Section: Discussionsupporting
confidence: 60%
“…A retrospective cohort study in Côte d’Ivoire among FSWs found low levels of retention on ART of 75% after 6 months of initiation on ART and this dropped to 68% at 12 months [ 16 ]. Another retrospective cohort study among KPs in Nigeria showed a decline in care from 63.5% at ART initiation to 55.4%, after one year of follow up on ART [ 17 ]. Both studies showed a linear trajectory of decline in retention in care among FSWs consistent with what we observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abubakar Saleh categorized these barriers to ART treatment into three main groups: health system-related, patient-related, and community-related barriers [ 13 ]. Health system-related barriers include poor treatment literacy, long waiting times, inadequate health infrastructure, limited availability of ART medications, and the facility not implementing person-centred or integrated approach [ 8 , 9 ]. Patient-related barriers encompass factors such as denial of HIV status, socioeconomic status, transportation, poor awareness, fear of adverse drug effects, and the stigma associated with HIV/AIDS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%